Tourism and conservation units: theoretical-conceptual and empirical analysis of the category indirect use in Brazilian national parks - Campos, Raul Ivan Raiol de; Pinto, Paulo Moreira; Cruz, Silvia Helena Ribeiro; Mendes, Fabrício Lemos de Siqueira (Revista Turismo em Análise, 2021)
The National System of Conservation Units defines indirect use as that which does not involve consumption, collection, damage, or destruction of natural resources. In this context, this research questions, from a theoretical and empirical applicability, the existence of an indirect use of natural resources by tourist activity and by residents in the National Parks of Lençóis Maranhenses, Jericoacoara, and Chapada das Mesas. In this set, its centrality is based upon analyzing the concept of indirect use and its applicability in these loci. For that, it uses classic authors who discuss common use resources, comparing them with contemporary researchers. The methodology consists of bibliographic and documentary research, field research, direct observation, and qualitative approach. Thus, based on theoretical assumptions and empiricism, the results demonstrate that what is practiced in these Conservation Units is the direct use of common use resources both by tourism and residents.